Large-eddy simulation and mathematical model of vortex breakdown and pressure drop in a cavity with tubeless vortex reducer - Wenjie Shen; Suofang Wang; Xindan Zhang; Xiaodi Liang (Engineering Applications of Computational Fluid Mechanics, 2022)
The tubeless vortex reducer was used to reduce the pressure drop in a cavity with radial inflow. In previous studies, the mechanism of vortex breakdown in tubeless vortex reducers was not clear, and there was a lack of direct guidance for engineering design. In this paper, we studied the vortex and pressure in the cavity in detail by large-eddy simulation (LES) and experiments. A mathematical model, which has high applicability and compatibility, was established to guide the pre-design of tubeless vortex reducers. The LES results showed that the high-speed and large-scale vortices broke rapidly at the nozzle inlet and reached the minimum size at the nozzle outlet. Furthermore, the enhancement of vortex in the downstream cavity was restrained. When the rotating speed was relatively low, strong negative vortices formed and the pressure drop increased in the downstream cavity. The experiments showed that the nozzle performance directly affected the flow characteristics and pressure drop in the cavity. Compared with the simple cavity, the tubeless vortex reducer generated lower pressure drop. The average relative error between the mathematical model and the experimental results was only 9.3%.